Phosphoproteome Analysis Reveals Phosphorylation Underpinnings in the Brains of Nurse and Forager Honeybees (Apis mellifera) - Gebreamlak Bezabih (Nature Portfolio, 2017)
Abstract The honeybee brain is a central organ in regulating wide ranges of honeybee biology, including life transition from nurse to forager bees. Knowledge is still lacking on how protein phosphorylation governs the neural activity to drive the age-specific labor division. The cerebral phosphoproteome of nurse and forager honeybees was characterized using Ti4+-IMAC phosphopeptide enrichment mass-spectrometry-based proteomics and protein kinases (PKs) were predicted. There were 3,077 phosphosites residing on 3,234 phosphopeptides from 1004 phosphoproteins in the nurse bees. For foragers the numbers were 3,056, 3,110, and 958, respectively. Notably, among the total 231 PKs in honeybee proteome, 179 novel PKs were predicted in the honeybee brain, of which 88 were experimentally identified. Proteins involved in wide scenarios of pathways were phosphorylated depending on age: glycolysis/gluconeogenesis, AGE/RAGE and phosphorylation in nurse bees and metal ion transport, ATP metabolic process and phototransduction in forager bees. These observations suggest that phosphorylation is vital to the tuning of protein activity to regulate cerebral function according to the biological duties as nursing and foraging bees. The data provides valuable information on phosphorylation signaling in the honeybee brain and potentially useful resource to understand the signaling mechanism in honeybee neurobiology and in other social insects as well.